Composition comprising phaleria leaf extract having anti-cancer activity - Abdullah, Luqman Chuah; Saiful Yazan, Latifah; Awang Biak, Dayang Radiah; Pin, Kar Yong; Yusuf, Umi Kalsom; Ismail, Nor Fariza; Nurdin, Armania; Ismail, Adawiah (2013)
The present invention discloses a composition comprising Phaleria leaf extract as active ingredient, which can be used as pharmaceuticals or food for treatment or prevention of cancer by way of inhibiting the proliferation of carcinoma cells.